Comparison of Methanol, Ethyl Acetates and Chloroform Extracts of Zingiber zerumbet (L) Smith in Larvisidal Activities on Aedes aegypti (Diptera: Culicidee) Larvae - Tri Murini; Mae Sri Hartati Wahyuningsih; Tri Baskoro T.Satoto (Majalah Farmaseutik, 2017)
The resistance of mosquito larvae to conventional larvicides has been increased in the recent years. Therefore, it is necessary to develop new larvacides from natural materials. Previous studies showed that Zingiber zerumbet (L.) Smith has a potential ability as a larvicide in Artemia salina Leach and Anopheles nunestovary. Nevertheless, the use of different solvents to observe the best larvicidal activity has not been known. This study aims to assess the larvicidal activity of methanol extract, ethyl acetate, and chloroform in Aedes aegypti  larvae. This is an exploratory laboratory study with the posttest-only control group. The extraction solvents used were methanol, ethyl acetate, and chloroform. Twenty-five instar larvae (III-IV) of Ae.aegypti were treated with seven different concentrations of the three Z. rhizome extracts. The mortality rate of the larvae was calculated and analyzed using probit analysis regression to obtain LC50 and LC90 values. The LC50 of the methanol, ethyl acetate, and chloroform extracts are 153.57, 185.80, 3542.03 ppm; while the LC90 are 226.59, 274.70, and 5567.24 ppm, respectively. The study suggested that the methanol extract of Z. zerumbet rhizome has the most robust larvicidal activity against third-fourth instar larvae of Ae. aegypti among other extracts.